An Improved Method for Optical Characterization of Mineral Dust and Soot Particles in the El Paso-Juárez Airshed - Polanco Gonzalez, Javier (2020)
Highly time-resolved aerosol measurements and analysis are necessary for a proper aerosol characterization in many polluted regions, because aerosol concentrations in polluted environments can change over time scales of minutes. However, many urban measuring sites have measuring devices that provide time resolved average aerosol concentrations over a day or two at best. Light-scattering properties of mineral dust and soot particles in the El Paso-Juárez Airshed were analyzed with an improved methodology, using the T-matrix, a maximum likelihood estimator (MLE), and data from both an acoustic extinctiometer and a laser particle counter. The hourly inter-comparisons of the scattering coefficients’ results between the model and those obtained using the instruments at a wavelength of 0.87 micro meters show good agreement. This methodology has been applied in the El Paso-Juárez Airshed successfully, and it could be used in other cities where mineral dust and soot are major components of the aerosol concentrations.